The use of nutritional supplements in dressage and eventing horses - Agar, C.; Gemmill, R.; Hollands, T.; Freeman, S.L. (BMJ Publishing Group:, 2016)
The aim of the study was to determine which types of nutritional supplements were used in dressage and eventing horses, and the reasons that owners used supplements. An online questionnaire was distributed through British Eventing and Dressage websites, to collect data on demographics of owners and their horses, supplements used and their opinion on health and performance problems. Data were evaluated using descriptive analysis, Sign and Fisher's exact tests for quantitative data, and categorisation of qualitative data. In total, 599 responses met the inclusion criteria (441 dressage and 158 eventing horse owners). Participants had 26.4 (3–60) (mean (range)) years of riding experience, owned 1.2 (0–10) horses and used 2 (0–12) supplements in their highest performing horse. The main health and performance issues identified for dressage were ‘energy/behaviour’, ‘lameness’ and ‘back and muscle problems’. The main issues for eventing were ‘stamina and fitness levels’,’ lameness’ and ‘energy/behaviour’. The main reasons for using supplements in their highest performing horse were ‘joints and mobility’, and ‘behaviour’ for dressage, and ‘electrolytes’, and ‘joints and mobility’ for eventing. Lameness and behavioural problems were significant concerns within both disciplines. There was incongruence between owners’ opinions of problems within their discipline and their reasons for using supplements.